Tradisi Manaqib Syekh Abdul Qodir Al-Jailani di Mushalla Raudlatut Thalibin Kembaran Kebumen - Slamet Yahya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2020)
This article aims Abstract to examine the tradition of manaqib of Sheikh Abdul Qodir Al-Jailani at the Mushalla Raudlatut Thalibin, Kembaran, Kebumen. The tradition of reading the manaqib also its existence is historical with the culture and psychology of the people from time to time and then its existence certainly affects the change in community behavior in some or all aspects of the life of the culprit. The tradition of manaqib in Mushala Raudlatut Thalibin is held every night on the 11th of qomariyah month, this election is in accordance with the date of the death of Sheikh Abdul Qodir al-Jailani ie on the 11th of rabi'ul tsani 561 H / 166 AD, with readings according to the guidance of the murshid. He wisdom to preserve the culture of our ancestors as long as it does not conflict with the texts of the Qur'an and the Hadith, expects a blessing from Sheikh Abdul Qodir al-Jailani to be classified as those who love waliyullah, contain moral educational values, and provide assemblies for the meet- ing of the congregation and the community. Tulisan Abstrak: ini bertujuan untuk mengkaji tentang tradisi manaqib Syaikh Abdul Qodir Al-Jailani di Mushalla Raudlatut Thalibin, Kembaran, Kebumen. Tradisi pembacaan manaqib juga keberadaannya menyejarah dengan budaya dan psikologi masyarakat dari waktu ke waktu yang kemu- dian keberadaannya tentunya berpengaruh pada perubahan tingkah laku masyarakat di sebagian atau di semua aspek kehidupan masyarakat pe- lakunya. Tradisi manaqib di Mushala Raudlatut Thalibin dilaksanakan setiap malam tanggal 11 bulan qomariyah, pemilihan ini sesuai dengan tanggal wafatnya Syekh Abdul Qodir al-Jailani yaitu pada tanggal 11 Rabi’ul Tsani 561 H/ 166 M, dengan bacaan-bacaan sesuai dengan panduan dari para mursyid. Hikmahnya untuk melestarikan budaya dari para leluhur kita selama tidak bertentangan dengan nash al-Qur’an dan Hadits, mengharapkan limpahan berkah dari Syekh Abdul Qodir al-Jailani, supaya tergolong orang-orang yang cinta kepada waliyullah, mengandung nilai-nilai pendidikan akhlak, menyediakan majlis untuk bertemunya para jama’ah dan masyarakat.